Phytochemicals: a promising approach to control infectious bursal disease - Tahir, Ifrah; Alsayeqh, Abdullah F. (Frontiers in Veterinary Science, 2024)
Infectious bursal disease (IBD) is one of the dangerous diseases of poultry that affects the bursa of Fabricius, which is an important organ of the bird's immune system. IBD virus is resistant to many drugs, making its control difficult. Vaccination of IBD is in practice for a long time worldwide to control IBD, but secondary issues like vaccine failure and lower efficacy lead to their reduced use in the field. Multiple medicines are currently used, but the phytochemicals have emerged as promising agents for controlling IBD. The drugs to be developed should possess direct antiviral properties by targeting viral entry mechanisms, enhancing the host immune response, and inhibiting viral protein synthesis. Phytochemicals have potential to contribute to food security by minimizing the possibility of disease outbreaks and ensuring that consumers worldwide obtain healthy poultry products. It has been now claimed that direct and indirect activities of phytochemicals can be effective in the control of IBDV. Although available evidence suggest that the phytochemicals can contribute in controlling occurrence IBDV, there is a definite need of focused studies to gain more insight and develop rational strategies for their practical use. This review highlights the disease caused by IBDV, inhibition of viral replication, boosting the immune system, disruption of viral membrane, and important phytochemicals showing antiviral activities against IBDV.